Insights into the Molecular Mechanisms Underlying Mammalian P2X7 Receptor Functions and Contributions in Diseases, Revealed by Structural Modeling and Single Nucleotide Polymorphisms - Jiang, Lin-Hua; Baldwin, jocelyn; Roger, Sébastien; Baldwin, Stephen (Frontiers in Pharmacology, 2013)
The mammalian P2X7 receptors (P2X7Rs), a member of the ionotropic P2X receptor family with distinctive functional properties, play an important part in mediating extracellular ATP signaling in health and disease. A clear delineation of the molecular mechanisms underlying the key receptor properties, such as ATP-binding, ion permeation, and large pore formation of the mammalian P2X7Rs, is still lacking, but such knowledge is crucial for a better understanding of their physiological functions and contributions in diseases and for development of therapeutics. The recent breakthroughs in determining the atomic structures of the zebrafish P2X4.1R in the closed and ATP-bound open states have provided the long-awaited structural information. The human P2RX7 gene is abundant with non-synonymous single nucleotide polymorphisms (NS-SNPs), which generate a repertoire of human P2X7Rs with point mutations. Characterizations of the NS-SNPs identified in patients of various disease conditions and the resulting mutations have informed previously unknown molecular mechanisms determining the mammalian P2X7R functions and diseases. In this review, we will discuss the new insights into such mechanisms provided by structural modeling and recent functional and genetic linkage studies of NS-SNPs.